Applications of Biosensors for Meat Quality Evaluations - Barbara Sionek; Wiesław Przybylski; Anita Bańska; Tomasz Florowski (Sensors, 2021)
The aim of this study was to apply biosensors in the assessment of meat quality. The research was carried out on 20 samples of the Longissimus muscle obtained from pork of Polish Landrace and Polish Large White hybrids of fattening pigs. In the samples, 48 h after slaughter pH values, color parameters in the CIE system (L* a* b*), the volume of natural drip loss and intramuscular fat content were measured. The commercially available biosensor Accutrend Plus was used to measure glucose, triglycerides and lactic acid in meat juice. Significant (p ≤ 0.05) relationships between glucose, triglycerides, lactic acid levels and pork quality characteristics, i.e., pH (r = −0.62; r = −0.78; r = −0.68 respectively), natural drip loss and (r = 0.57; r = 0.58; r = 0.49), color parameters as L*, a* and b* (r = from 0.47 to 0.79) were demonstrated. The study showed a negative correlation between the intramuscular fat content and acidification of muscle tissue (r = −0.49), and a positive one with the brightness of color (r = 0.46). The results of the canonical analysis show that the measurement of all three metabolites in muscle juice allows the evaluation of the technological quality of meat with an accuracy of 86.54% (Rc = 0.93, p < 0.01).